KINERJA TENAGA PENDIDIK PASCASERTIFIKASI - Muflihin, Hisbul (IAIN Pekalongan, 2012)
Teachers are professional educators, and the professionalism requires that each concerned will be able to demonstrate a good work in accordance with the four competencies as an educator. To be a professional educator, a teacher or a lecturer is required to take a series of procedures, among others are: having minimum education degree/certificate of teaching and attending the PLPG (Education and Training of Professional Teacher). PLPG is an absolute rule that must be taken by the teachers to get the certain amount of profession allowance. Thus, the main objective to join up the PLPG should be to ensure that the way the workdone by the teachers is really be based on professionalism itself and is not merely to seek professional allowance alone. By receiving allowance, an educator should be to stay motivated and dedicated in carrying out their main duties in educating and teaching. The performance condition after the certification of these educators proved to be the opposite; as shown by the results of the study that indicate that they are less motivated and do not have a high self-actualization. This condition isof course very poor (not in accordance with what isexpected by the government). Hence a certain approach is required - that could be considered capable of restoring the work ethic and self-motivation as educator. Among those are the religious approach and process one by BARS technique scoring.